A era das redes de a África : Internet, seus usos e perspectivas em Cabo Verde - Tavares, Orlando Mendes (2006)
This study discusses the globalization and the question of new technology of information and communications, the situation and the including of African continent in that context. I intentend to demonstrate how the african countries are adapting themselves in the new tecnologies, specially the internet, then which current strategies for a better use of the resources of sustainable development. My aim is to investigate the appropriations and perspectives of the internet em Cape Verde, for a research on collecting databases and documentations in public and private institutions including a serie of interviews with managers of various companies, civil societies and governments.